2 - Use of the Term ‘Empire’ in Historical Research on Africa: A Comparative Approach - Michal Tymowski (Afrika Zamani, 2022)
This paper explores the use of the term ‘empire’ in historical research on Africa to illustrate the problem of ‘comparability’ and the requirement for measure- ment and appropriateness of the ‘measurement language’. Taking the reader through a review of the literature, beginning with Maurice Delafosse's populari- sation of the concept in his essays on ancient Ghana, Mali and Songhai in 1912 and climaxing with pointers in the multi-volume UNESCO General History of Africa in the late twentieth century, the author exposes the essential inconsist- ency in African and Africanist use of the term, ‘empire’, which inevitably crept into the study of African history in the heydays of ‘conceptual Eurocentrism’. He maintains that the usage of the term ‘empire’ in African historiography was employed due to the need to name those African states which were extensive territorially and multi-ethnically; and states designated ‘empires’ were charac- terised by certain elements of an imperial organisation rather than by a fully formed imperial system. And for analogues and comparisons, the form of de- pendence between the centre and the subordinated tribes and early states that developed in Africa reminds us rather of the relations existing on the other con- tinents in the early stages of large state formation. Hence, the term ‘early em- pire’ seems more justified to describe these states in research on the history of Africa. The author calls for the need to conduct discussion, with the help of a comparative method, on the specific features of those ‘early empires’.